Fact-Finding Survey and Exploration of Preventive Drugs for Antineoplastic Drug-Induced Oral Mucositis Using the Japanese Adverse Drug Event Report Database - Hajime Matsuo; Kiri Endo; Hiroyuki Tanaka; Toshihisa Onoda; Toshihiro Ishii (MDPI AG, 2024)
Oral mucositis (OM) is one of the most common adverse events associated with antineoplastic drug treatment. Studies on the risk of antineoplastic drug-induced OM and its prevention are limited. We, therefore, conducted a disproportionality analysis of antineoplastic drug-induced OM and explored candidate preventive drugs for OM using the Japanese Adverse Drug Event Report (JADER) database. The JADER database showed that between April 2004 and March 2022, antineoplastic drug-related adverse events were reported in 210,822 cases, of which 2922 were OM. Forty-two drugs appeared to be associated with OM. The weibull distribution showed different patterns of time-to-onset depending on the type of antineoplastic drug administered. Cluster analyses classified antineoplastic drugs according to the typical symptoms of OM. These findings suggest that antineoplastic drug-induced OM should be monitored based on expression patterns of symptoms. Upon analyzing the inverse association, several concomitant drugs, including lenalidomide hydrate and febuxostat, were expected to be candidate preventive drugs for antineoplastic drug-induced OM. Concomitant drugs that showed an inverse association with antineoplastic drug-induced OM differed within the Anatomical Therapeutic Chemical classification. These findings could serve as a reference when considering drugs that should be prioritized to validate their prophylactic effect against antineoplastic-induced OM in the future.